2015
DOI: 10.4236/pp.2015.67034
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Anti-HIV Activity of Partially Purified Coumarin(s) Isolated from Fungal Endophyte, <i>Alternaria</i> Species of <i>Calophyllum inophyllum</i>

Abstract: 5 totally different endophytic fungal species were isolated from bark and leaf parts of Calophyllum inophyllum. Leaf part yielded Trichoderma harzianum and Alternaria species, whereas bark showed the presence of Fusarium species, Aspergillus species and unidentified fungi. Two solvents (hexane and methanol) were used for endophytic fungal extraction and the Alternaria species had shown the presence of coumarin whereas Trichoderma harzianum in methanol extract and Fusarium species in hexane extract had shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The similar types of phytochemicals were also observed from different endophytes 2H-1-Benzopyran-2-one [24], 3-Benzofurancarboxylic acid [25], Hymecromone [26], 16-Octadecanoic acid, methyl ester [27], alloisoimperatorin [28], Z,E-2-Methyl-3,13-octadecadien-1-ol [29], [Z]-Cinnamic acid, 2-diphenylmethyleneamino-, methyl ester [30].…”
Section: Ijppe Volume 13supporting
confidence: 66%
See 1 more Smart Citation
“…The similar types of phytochemicals were also observed from different endophytes 2H-1-Benzopyran-2-one [24], 3-Benzofurancarboxylic acid [25], Hymecromone [26], 16-Octadecanoic acid, methyl ester [27], alloisoimperatorin [28], Z,E-2-Methyl-3,13-octadecadien-1-ol [29], [Z]-Cinnamic acid, 2-diphenylmethyleneamino-, methyl ester [30].…”
Section: Ijppe Volume 13supporting
confidence: 66%
“…The C. uredinicola extract had shown inhibition of HIV-1 proteins viz., protease, RT, protease and gp120. The C. uredinicola was inhibited RT activity strongly (83.81+2.14) and it was high compared to standard AZT (74.36+1.89) (Table 3) [27,43]. Similarly, the gp120 (80.24+2.4) (Table 4), protease (77.63+2.14) ( Table 5), integrase (79.43+2.14) ( Table 6) proteins activity was decreased due to C. uredinicola extract.…”
Section: Treating Agentsmentioning
confidence: 96%
“…Alternaria species in endophytic lifestyle have been shown to exhibit anti-HIV activities and some of the active compounds and their mechanism of action have been elucidated ( Wellensiek et al, 2013 ; Eram et al, 2018 ). For example, in a study by Bashyal et al (2014) they isolated alterotoxins from A. tenuissima and Govindappa et al (2015) isolated coumarins from Alternaria species.…”
Section: Discussionmentioning
confidence: 99%
“… Ma et al (2013) reported anti-HIV reverse transcriptase activity of a PHP protein isolated from Peganum harmala seeds with 50% inhibitory concentration at 1.5 µM. Govindappa et al (2015) revealed that partially purified coumarins isolated from fungal endophytes, Alternaria sp. displayed high inhibition on three viral enzymes, HIV-1 Reverse Transcriptase, which was inhibited by 82.81% (control, heparin = 74.54% inhibition), integrase enzyme activity which was inhibited by 98% and protease activity was inhibited by 78%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation